The Effect of E-Learning on The Learning Effectiveness of PKK Students at Padang State University - Hidayat, Kurnia; Gusnita, Wiwik; Kasmita, Kasmita; Siregar, Juliana (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study analyzes the effect of Moodle-based E-Learning on the learning effectiveness of undergraduate students of PKK Culinary Arts at Padang State University. With a quantitative correlational design and a sample of 176 students selected purposively, data were collected through a Likert scale questionnaire and analyzed using normality, linearity, and simple regression tests. The results showed a positive and significant influence between the use of E-Learning and learning effectiveness (R² = 0.320; p = 0.000 < 0.05). The contribution of E-Learning was 32%, while 68% was influenced by other factors such as motivation, teaching methods, and the learning environment. These findings confirm that E-Learning is an effective medium that increases the independence and flexibility of vocational students' learning.